2022
DOI: 10.1093/cid/ciac807
|View full text |Cite|
|
Sign up to set email alerts
|

Twice-Daily Oral Zinc in the Treatment of Patients With Coronavirus Disease 2019: A Randomized Double-Blind Controlled Trial

Abstract: BACKGROUND Zinc supplementation has been considered one of the potential therapies for coronavirus disease-19 (COVID-19). We aimed to examine zinc efficacy in adult patients with COVID-19 infection. METHODS We conducted a prospective, randomized, double-blind, placebo-controlled, multicenter trial. Patients tested positive for COVID-19 without end organ failure were randomized to oral zinc (n = 231) or matching placebo (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
56
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 20 publications
0
56
0
2
Order By: Relevance
“… 6 Overall, the findings of this RCT suggest the promising role of zinc in the treatment of patients with COVID-19. 6 However, previous RCT by Thomas et al reported that zinc could not significantly decrease the duration of symptoms and was early terminated for futility. 7 Similar, the RCT by Abd-Elsalam et al did not find the additional clinical benefit of zinc supplement.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“… 6 Overall, the findings of this RCT suggest the promising role of zinc in the treatment of patients with COVID-19. 6 However, previous RCT by Thomas et al reported that zinc could not significantly decrease the duration of symptoms and was early terminated for futility. 7 Similar, the RCT by Abd-Elsalam et al did not find the additional clinical benefit of zinc supplement.…”
mentioning
confidence: 73%
“…Recently, one randomized controlled trial (RCT), which investigated the clinical efficacy of zinc supplement for patients with COVID-19. 6 Ben Abdallash et al found that compared with placebo, treatment with oral zinc was associated with a lower 30-day mortality, ICU admission rate and shorter duration of symptoms and length of hospital stay. 6 Overall, the findings of this RCT suggest the promising role of zinc in the treatment of patients with COVID-19.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons, the well-designed and executed study published in this issue of Clinical Infectious Diseases by Abdallah et al [8] represents an important methodological advancement. This carefully designed trial with recruitment of a much larger population compared with the few previous trials was therefore able to achieve a considerably higher statistical precision of the effect estimates, in addition to performing a careful randomization of the participants and blinding of both study subjects and investigators.…”
mentioning
confidence: 99%